IMPLEMENTASI ALGORITMA APRIORI DALAM MENENTUKAN PERSEDIAAN OBAT - Gusti Ahmad Syaripudin; Edi Faizal (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2017)
Computer-based transaction resulting in the accumulation of data in the database of an application. The data can be reprocessed to obtain important information. Data mining can be used to obtain valuable information for management purposes. The technique can be used are the rules of the association. One type of association rules is a priori algorithm. Application of a priori algorithm has been done in the analysis of sales. The research will be applied to the application pharmacies RMC. The programming language used for the algorithm implementation language is Java with Netbeans Platform 7.4 .DBMS used is MySQL. The test results showed a priori algorithm can be used to identify drugs that may be purchased in conjunction with other drugs, as well as showing the drug most widely sold and least by the set of combinations of items. Such recommendations can be used for management in determining drug supply and design marketing strategies quickly, accurately and efficiently.Keywords: java, apriori algorithm, netbeans, MySQL